2010
DOI: 10.1016/j.ijrobp.2010.02.020
|View full text |Cite
|
Sign up to set email alerts
|

Melanin-Covered Nanoparticles for Protection of Bone Marrow During Radiation Therapy of Cancer

Abstract: Purpose Protection of bone marrow against radiotoxicity during radioimmunotherapy and in some cases external beam radiation therapy such as hemi-body irradiation would permit administration of significantly higher doses to tumors, resulting in increased efficacy and safety of treatment. Melanin, a naturally occurring pigment, possesses radioprotective properties. We hypothesized that melanin, which is insoluble, could be delivered to the bone marrow by intravenously administrated melanin-covered nanoparticles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
78
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(80 citation statements)
references
References 25 publications
1
78
0
1
Order By: Relevance
“…It was reported that melanin isolated from the fungus G. simplex reduced the radiation-induced overproduction of pro-inflammatory cytokines (IL-6 and TNF-α), which might help in the recovery from radiation injury by preventing the aggravation of inflammation and oxidative stress [33]. This study confirmed the possible use of melanin-coated nanoparticles for protecting against radiotoxicity during radioimmunotherapy [117].…”
Section: Biological Activities Of Melaninsupporting
confidence: 73%
See 1 more Smart Citation
“…It was reported that melanin isolated from the fungus G. simplex reduced the radiation-induced overproduction of pro-inflammatory cytokines (IL-6 and TNF-α), which might help in the recovery from radiation injury by preventing the aggravation of inflammation and oxidative stress [33]. This study confirmed the possible use of melanin-coated nanoparticles for protecting against radiotoxicity during radioimmunotherapy [117].…”
Section: Biological Activities Of Melaninsupporting
confidence: 73%
“…A study performed with melanin nanoparticles as biocompatible drug nanocarriers, using metronidazole (antibiotic drug), showed that melanin could be a very interesting nanocarrier drug release device because it strongly responds to pH, being a very interesting feature for the treatment of intestine and colon diseases, which would greatly benefit with pH targeting [142]. Another study showed that systemic melanin-covered nanoparticle (MN) administration reduced hematologic toxicity in mice treated with radiation and that these structures provide efficient protection to bone marrow against radiotoxicity during radioimmunotherapy and in some cases external beam radiation therapy, permitting the administration to tumors of significantly higher doses [117].…”
Section: Medical Applicationsmentioning
confidence: 99%
“…To date, there are still a limited number of chemical RAs clinically used to minimize the severity and duration of toxicities associated with radiotherapy. Some other agents such as palifermin [121] , genistein [122] , angiotensin I-converting enzyme inhibitors [123] , melanin [124] , hemocyanin [125] and Vitamin D [126] showed a promising effect against the radiation toxicity, however there is a lack of high quality clinical studies for most of the agents described. The evaluation of safety and efficacy of these emerging agents are needed and their effects on tumor sensitivity should be verified [117] .…”
Section: Ra Its Categoris and Mechanisms Of Functionmentioning
confidence: 99%
“…It is shown that Sepia melanin can be nanonized and dispersed in pure water or biological medium by processing of melanin powder in suspension with a magnetic stirrer running for 48 h. It is also shown that irradiation of Sepia melanin in suspension with femtosecond laser pulses can result in photo-fragmentation, which leads to nanonization and dispersibilization at a rate higher than that with mechanical stir. In this report and our previous work [9] we have demonstrated that both Sepia melanin (natural melanin) and synthetic melanin can be nanonized and dispersed in pure water or biological medium by processing of melanin powder in suspension with a magnetic stirrer running for 48 h. Although water-dispersible melanin processed with the techniques reported herein would not be practical photosensitizer for PDI, we expect it could be utilized in other applications such as adjuvant in radiation therapy [38], antioxidant [4,5,9,39], metal-ion scavenger [40], antidote for acute radiation syndrome [38], antitumor drug [41,42], antivenin drug [43], antivirus [44] and contrast-enhancing agent in magnetic resonance imaging (MRI) [45,46].…”
Section: Resultsmentioning
confidence: 77%